O estatuto do real em Lacan: dos primeiros escritos ao seminário VII, A ética da psicanálise - Chaves, Wilson Camilo (2006)
The present work seeks to elucidate the notion of Real in Lacan, from the first writings to the seminar VII, The Ethics of the Psychoanalysis. Initially, the relationships are privileged: Imaginary and Real; Symbolic and Real; Symbolic, Imaginary and Real. After the elucidation of those relationships, it is advanced for the moment of transition of the concept of Real, redoing Seminars IV, V, VI and some referring texts to them. Here, Lacan is verified retaking the present idea from the seminar III, The Psychoses, that the Real is what always comes back to the same place. It is arrived, like this, to the seminar VII, dedicated to the Ethics of the Psychoanalysis, in that is shimmered the relationship among the Real and das Ding. He/she/you sees her, here, that the Real is of the order of das Ding. The Ethics of the Psychoanalysis, of that sorts things out, it is centralized in that Real one and it emphasizes the sublimation as the one that elevates the object to the dignity of das Ding. The work is concluded affirming that Lacan, more ahead in your teaching, it will formulate the Real as being of the order of the impossible, as well as it will be served as the knot borromeano, interlacing, once and for all, the three registrations: Real, Symbolic and Imaginary.